How soundscape perception enhances the well-being of elderly recreational visitors in urban parks: a case study of Zhengzhou People’s Park - Ning Li; He Wang; Jianpeng Fan (Scientific Reports)
Abstract As the pace of urban life accelerates, an increasing number of people fall into a sub-healthy state. In response, there is a growing desire among individuals to enhance life satisfaction and well-being by reconnecting with natural environments. Against this backdrop, urban parks have become popular destinations for recreational activities, providing opportunities for relaxation. Natural soundscapes, as critical ecosystem services, exert positive effects on physical and mental health. This study analyzed 446 survey responses using SPSS 25.0 and Mplus 8.0 to explore how soundscape perception related to the well-being of elderly recreational visitors in urban parks. The results were as follows: Firstly, there was a positive correlation between the soundscape perception of elderly recreational visitors and their well-being. Secondly, place attachment acted as a mediator in the relationship between soundscape perception and well-being for these elderly visitors. Thirdly, restorative perception also played a mediating role in this relationship. Fourthly, place attachment and restorative perception jointly played a serial mediating role in the association between the soundscape perception and well-being of elderly recreational visitors. Finally, leisure involvement moderated the relationship between soundscape perception and the well-being of elderly recreational visitors. These findings contribute to ecosystem services and public health theories, while providing practical guidance for enhancing elderly visitors’ health and well-being.